An international field study of the ICD‐11 behavioural indicators for disorders of intellectual development. Issue 4 (16th February 2022) - Lemay, K. R.; Kogan, C. S.; Rebello, T. J.; Keeley, J. W.; Bhargava, R.; Sharan, P.; Sharma, M.; Kommu, J. V. S.; Kishore, M. T.; de Jesus Mari, J.; Ginige, P.; Buono, S.; et al.
Abstract: Background: The World Health Organization (WHO) has approved the 11th Revision of the International Classification of Diseases (ICD‐11). A version of the ICD‐11 for Mental, Behavioural and Neurodevelopmental Disorders for use in clinical settings, called the Clinical Descriptions and Diagnostic Requirements (CDDR), has also been developed. The CDDR includes behavioural indicators (BIs) for assessing the severity of disorders of intellectual development (DID) as part of the section on neurodevelopmental disorders. Reliable and valid diagnostic assessment measures are needed to improve identification and treatment of individuals with DID. Although appropriately normed, standardised intellectual and adaptive behaviour assessments are considered the optimal assessment approach in this area, they are unavailable in many parts of the world. This field study tested the BIs internationally to assess the inter‐rater reliability, concurrent validity, and clinical utility of the BIs for the assessment of DID. Methods: This international study recruited a total of 206 children and adolescents (5–18 years old) with a suspected or established diagnosis of DID from four sites across three countries [Sri‐Lanka ( n  = 57), Italy ( n  = 60) and two sites in India ( n  = 89)]. Two clinicians assessed each participant using the BIs with one conducting the clinical interview and the other observing. Diagnostic formulations using the BIs and clinical utility ratings were collected and entered independently after each assessment. At a follow‐up appointment, standardised measures (Leiter‐3, Vineland Adaptive Behaviour Scales‐II) were used to assess intellectual and adaptive abilities. Results: The BIs had excellent inter‐rater reliability (intra‐class correlations ranging from 0.91 to 0.97) and good to excellent concurrent validity (intra‐class correlations ranging from 0.66 to 0.82) across sites. Compared to standardised measures, the BIs had more diagnostic overlap between intellectual and adaptive functioning. The BIs were rated as quick and easy to use and applicable across severities; clear and understandable with adequate to too much level of detail and specificity to describe DID; and useful for treatment selection, prognosis assessments, communication with other health care professionals, and education efforts. Conclusion: The inclusion of newly developed BIs within the CDDR for ICD‐11 Neurodevelopmental Disorders must be supported by information on their reliability, validity, and clinical utility prior to their widespread adoption for international use. BIs were found to have excellent inter‐rater reliability, good to excellent concurrent validity, and good clinical utility. This supports use of the BIs within the ICD‐11 CDDR to assist with the accurate identification of individuals with DID, particularly in settings where specialised services are unavailable.